Penyelesaian Sengketa terhadap Bilateral Investment Treaty (BIT) antara Home State dengan Host State - Mochammad Fikhran Noer Alimuddin (CV Edujavare Publishing, 2024)
Political and economic instability in host countries often trigger disputes in foreign investments due to policy shifts, environmental regulations, and human rights issues, straining relations between home and Host States. This study scrutinizes Bilateral Investment Treaties (BIT) provisions on dispute resolution, assessing common sources of contention and examining dispute resolution cases to understand BIT mechanisms practically. It also evaluates Law No. 25 of 2007 on Capital Investment's role in resolving investment disputes in Indonesia, offering recommendations to enhance BIT dispute resolution for a more stable investment climate. Employing a normative juridical method and qualitative analysis, data was collected through literature reviews of laws, treaties, legal documents, and case studies. The findings highlight BIT dispute resolution aims to protect investor rights, mitigate legal uncertainties, and facilitate impartial resolution. Challenges persist in Law No. 25 of 2007 implementation, underscoring the need for transparency and legal certainty. Recommendations include increasing transparency, ensuring arbitrator independence, aligning with Sustainable Development Goals (SDGs), involving civil society, and harmonizing with national legal systems.